Pelatihan Akuntansi Keuangan Lembaga Bagi Guru Smk Dalam Menyiapkan Tenaga Operator Keuangan Desa Dalam Masa Pandemi (Mgmp Akuntansi Kota Pekanbaru) - Gusnardi Gusnardi; Amir Hasan; Suarman Suarman; Nasrizal Nasrizal; RM Riadi (Jurnal Pengabdian UntukMu NegeRI, 2020)
These service activities are aimed at; 1) provide insight into knowledge about institutional financial accounting, 2) Provide insight into knowledge about the importance of teacher understanding and mastery of institutional financial accounting material, 3) Provide the ability to develop personnel and knowledge of institutional financial accounting by seeking information related to the material, and 4) Providing provisions to Pekanbaru City Accounting MGMP teachers regarding learning models that can be carried out by teachers online, for example using google classrooms, zoom meetings, google meetings. The method of approach that will be taken to complete this program is to use the method of lectures, tutorials, and discussions. This training for teachers was held for 5 days in 5 different SMKs in Pekanbaru City. From this training, it is hoped that SMK teachers will be able to educate financial accounting institutions, especially village financial accountants, using online media, so that they can use this training as a means of ongoing training during the Covid-19 pandemic.